Evaluating fluticasone furoate + vilanterol for the treatment of chronic obstructive pulmonary disease (COPD). (13th June 2019) - Lal, Chitra; Strange, Charlie
ABSTRACT: Introduction : Inhaled corticosteroid/long-acting β-2 agonists (ICS/LABA) combination inhalers have been a lifeline for a generation of chronic obstructive pulmonary disease (COPD) and asthma patients. Fluticasone furoate and Vilanterol (FF/VI) as a once-daily ICS/LABA combination have an extensive clinical trial and real-world data to support its use in COPD patients. Areas covered : The authors provide pharmacological profiles of fluticasone furoate, vilanterol and the FF/VI fixed dose combination. Salient clinical trials evaluating efficacy and safety of the FF/VI combination, and studies demonstrating the impact on COPD exacerbation risk and mortality are also discussed. Expert opinion : ICS/LABA combinations provide bronchodilation and decrease the frequency of COPD exacerbations. Individualizing treatment of each COPD patient based on unique phenotypes will maximize chances of therapeutic responsiveness. Asthma-COPD overlap (ACO), patients with sputum and/or blood eosinophilia, patients with a brisk bronchodilator response, and patients with frequent exacerbations are more likely to show a therapeutic response to ICS than populations who have none of these features. FF/VI will likely remain a popular ICS/LBA combination to treat COPD, as a once-daily inhaled therapy delivered via the Ellipta device popular with COPD patients, with extensive clinical trial and real-world data to support its use.